2020
DOI: 10.1016/j.jval.2019.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilar Uptake in Medicare Part B Varied Across Hospital Outpatient Departments and Physician Practices: The Case of Filgrastim

Abstract: and compare characteristics of patients and facilities that used filgrastim-sndz or originator filgrastim (Neupogen).Methods: The 20% sample of Medicare Part B fee-for-service administrative claims data was used to extract information on claims for any filgrastim product between January 1, 2015 and December 31, 2017.Results: The utilization of filgrastim-sndz in Medicare Part B increased sharply between January and August 2016, surpassing filgrastim by November 2017, contributing to a 30% decrease in overall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 3 publications
3
13
0
Order By: Relevance
“…19 In addition, Socal et al used the 2015-2017 Medicare Part B claims data and found an improved uptake of biosimilar filgrastim in the Medicare Part B program. 20 This study used the most recently available Medicare and Medicaid drug spending data to evaluate the uptake and cost of filgrastim-sndz, relative to its originator filgrastim and alternative biologic tbo-filgrastim, among Medicare and Medicaid populations in 2015-2018.…”
Section: What This Study Addsmentioning
confidence: 99%
“…19 In addition, Socal et al used the 2015-2017 Medicare Part B claims data and found an improved uptake of biosimilar filgrastim in the Medicare Part B program. 20 This study used the most recently available Medicare and Medicaid drug spending data to evaluate the uptake and cost of filgrastim-sndz, relative to its originator filgrastim and alternative biologic tbo-filgrastim, among Medicare and Medicaid populations in 2015-2018.…”
Section: What This Study Addsmentioning
confidence: 99%
“…5 Under this policy structure, however, biosimilar uptake remains low and prices remain high, differing from the experience in the US Department of Veterans Affairs and European health care systems. [6][7][8][9][10][11] For example, in quarter 3 of 2018, Remicade (infliximab) still maintained 81% of the Medicare Part B market share of Remicade and 2 approved biosimilars, Inflectra (infliximab-dyyb) and Renflexis (infliximab-abda), even though the biosimilars were priced at a 17% to 23% discount off of the Remicade cost. 12 Given this background, 2 key gaps remain in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…This work supports previous evidence from studies of filgrastim, which suggest that patient characteristics are not strongly associated with biosimilar use. 15 Adjusted analyses controlling for patient and practice characteristics found that both physician specialty 15,16 and physician prescribing volume 15 of a given drug class remained strongly associated with biosimilar use. Although results were not consistent in the filgrastim drug class, physicians with a higher volume of prescriptions were generally more likely to prescribe biosimilar products.…”
Section: Discussionmentioning
confidence: 99%